The Black Sea Encyclopedia - Grinevetsky, S.R (Springer, 2015)
This publication is devoted to the natural feature – the Black Sea and its littoral states. At the same time the Azov Sea is also considered here. This region is the focus of many geopolitical, economic, social and environmental issues that involve not only the countries coming out to the Black and Azov Seas, but other world countries, too.